Nonconjugative Plasmids Encoding Sulfanilamide Resistance - Mitsuhashi, Susumu (1977)
Nonconjugative plasmids encoding sulfanilamide (Sa) resistance were demonstrated at a high frequency in Shigella and Escherichia coli strains resistant to sulfanilamide. These Sa plasmids were all compatible with the standard plasmids used in compatibility testing. The sizes of seven Sa plasmids were measured by electron microscopy and ranged from 1.79 to 2.08 μm, corresponding to 3.5 to 3.9 megadaltons.